Exploring the relationship between user experience, engagement, and post watching behavior in interactive movie across different age group - Trisnahadi, Nabila Nurshaina Aisha; Windasari, Nila Armelia (Journal of Business and Management, 2020)
Abstract. Interactivity is an emerging concept used in many aspects, including entertainment media. Recently, people are thrilled by the novel concept of interactive movies. Interactive movie combines the concept of video gaming with storyline of a movie. Along the story, audience are given some ptions to decide what the characters should do, therefore shaping the story as the audience’s wish, creating a new and exciting entertainment media. Apart from the interesting concept, the creation of interactive movie is very expensive. And due to the novelty of the interactive movie concept, there is limited studies on this topic. Therefore, this research aims to discover the audiences’ experience, engagement, post watching behavior, and how it correlates with each other. This research is using experiments and quantitative approach with Netflix interactive movies as the object for the research due to the popularity of the platform in Indonesia. The data was gathered from different age groups and analyzed using multiple linear regression and analysis of variances. This study found that audiences’ experience on all age groups are similar, with the best interactive movie experience derived from teenagers category. The relationship between experience, engagement, and post watching behavior results are different across age groups. Netflix was suggested to emphasize the emotional stance to captivate audiences, and creating a more fun and engaging system to develop better post watching behavior.Keywords: Interactive Movie; Age Groups; User Experience; User Engagement; Post Behavior; Netflix.